How to Teach Teamwork in a PBL Curriculum - Hernández, Carola Hernández; Ramos, Liliana Maritza Melo (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
The needs of the globalized world and the transformations that different organizations undergo make being competent in teamwork a necessity. Therefore, the education sector must give it the appropriate relevance and concern itself with developing this particular competence in higher education. A Colombian university has a course called Engineering and Science: A Shared World, which has a PBL curriculum and aims to train this competence explicitly. The course design included a theoretical presentation on what a team is and its main characteristics, postulated by Johnson, D.W., Johnson, R., & Smith, K. (1998), and activities to evidence these characteristics and their importance to work adequately. This text presents a case study that seeks to identify the learning outcomes related to teamwork within the PBL proposed in this course. To achieve this, qualitative information was collected through the products created during the course: the class activities, the contracts, a group of team health activities, the final reflections, and the co-assessments. This information was analyzed through predetermined categories based on the course objectives and the dimensions of teamwork; no new categories emerged. The data analysis revealed that students identified and conceptualized elements such as individual responsibility or face-to-face interaction properly and as essential for team building and development. Still, positive interdependence and a proactive approach to communication and conflict were challenging to conceptualize and exemplify. Finally, many of the students identified that although team monitoring activities were carried out in class concerning the progress of socio- emotional skills, such as anticipating conflict or managing agreements, it was new for them. Their teams did not take full advantage of these spaces that, reflecting on the entire process, were as important as monitoring the products to be delivered.